Strange things happen at sea: training and new technology in a multi-billion global industry. Issue 8 (16th November 2016) - Sampson, Helen; Tang, Lijun
Abstract : It is not unusual to find that employers operating in low-pay sectors are reluctant to provide vocational training. Frequently they fear benefitting competitors as better-skilled employees command a more competitive position in the labour market and may choose to leave one employer and take their newly acquired skills elsewhere. However, in contrast the expectation might reasonably be that employers in more skilled sectors would be more enthusiastic about such training particularly when the financial, environmental and human costs, of errors are high. This paper therefore analyses vocational training provision in the more skilled sector of professional seafaring. In this sector, accidents may cause massive environmental damage and loss of life, and may incur substantial fines and financial penalties. Using a mix of qualitative and quantitative data, the paper focuses upon the adequacy of the training that is provided to seafarer officers in relation to the introduction of new technology aboard their vessels.